Sustainability Analysis of Landfill Cover System Constructed Using Recycled Waste Materials by Life Cycle Assessment - G. Sanoop, Sobha Cyrus and G. Madhu (Nature Environment and Pollution Technology, 2024)
The sustainability of using industrial by-products for the construction of landfill cover was determined using Life Cycle Assessment (LCA). LCA was carried out on four materials: sand- bentonite mix, red earth- bentonite mix (amended soil), Waste Foundry Sand (WFS)- Bentonite mix, and WFS- marine clay mix. The former two are commonly used cover soils and the latter two are alternative materials proposed. Environmental impacts based on the extraction of resources, processing, transportation to the site, and site preparation were considered using the ‘cradle to site’ approach. Analysis was carried out in OpenLCA software using the ReCiPe (H) Midpoint method of impact assessment. Required data for analysis was taken from the Ecoinvent database supplemented with inputs from a field survey. The use of WFS in landfill cover systems was found to be sustainable using LCA studies when compared to conventional materials.